Switching speed in resistive random access memories (RRAMS) based on plastic semiconductor - Rocha, P. F. (2015)
This work addresses non-volatile memories based on metal-oxide polymer diodes. We make a thorough investigation into the static and dynamic behavior. Current-voltage characteristics with varying voltage ramp speed demonstrate that the internal capacitive double-layer structure inhibits the switching at high ramp rates (typical 1000 V/s). This behavior is explained in terms of an equivalent circuit. It is also reported that there is not a particular threshold voltage to induce switching. Voltages below a particular threshold can still induce switching when applied for a long period of time. The time to switch is longer the lower is the applied voltage and follows an exponential behavior. This suggests that for a switching event to occur a certain amount of charge is required. © 2011 Materials Research Society.